PERANCANGAN PRODUK JEMURAN PAKAIAN PORTABLE DENGAN MENGGUNAKAN QUALITY FUNCTION DEPLOYMENT - ADHYRIYANTO, YANUTAMA VIKO; Susanti, Elva (Computer Science and Industrial Engineering, 2020)
Designing portable clothesline products to meet customer needs using the Quality Function Deployment Method. This research was conducted in the city of Batam where a small city, very densely populated, with the majority of the population are company workers. Drying is a tiring job, and therefore effective, efficient drying is needed to make it easier for users to carry and store. The use of the Quality Function Deployment method goes through 4 phases of the process namely House of Quality (HOQ), design Deployment, manufacturing planing, Product Planing , by taking a sample of 122 respondents from three housing estates namely Puriagung, Genta Batuaji, and Villa Mukakuning. This study uses a validity and reliability analysis test using a significance level of 0.05 with 122 respondents from the results of r table 0.1779 declared valid, then reliability testing using cronbach alpha values ​​0.6, 60% with the results of 0.980, 0.968 and 0.760. from passing 4 phases in QFD produces portable clothesline with a total of 24 hook hangers, clothesline that can be folded on its side, and clothesline that can be set high and low. The attributes developed are based on certain considerations and the results of the respondent's questionnaire.